2023
DOI: 10.1101/2023.10.23.563644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome Editing Outcomes Reveal Mycobacterial NucS Participates in a Short-Patch Repair of DNA Mismatches

Tanjina Islam,
Eric A. Josephs

Abstract: In the canonical DNA mismatch repair (MMR) mechanism in bacteria, if during replication a nucleotide is incorrectly mis-paired with the template strand, the resulting repair of this mis-pair can result in the degradation and re-synthesis of hundreds or thousands of nucleotides on the newly-replicated strand (long-patch repair). While mycobacteria, which include important pathogens such asMycobacterium tuberculosis, lack the otherwise highly-conserved enzymes required for the canonical MMR reaction, it was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Such striking preference was also observed with NucS from T. kodakarensis ( 9 ) and C. glutamicum ( 20 , 21 ). Furthermore, recent oligonucleotide recombination experiments in M. smegmatis yet to be published ( 70 ) revealed that in vivo NucS would only correct G/T but not A/C mismatches in this species. In this case, transition events in MMR-deficient Δ nucS lines are due to uncorrected G/T mismatches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such striking preference was also observed with NucS from T. kodakarensis ( 9 ) and C. glutamicum ( 20 , 21 ). Furthermore, recent oligonucleotide recombination experiments in M. smegmatis yet to be published ( 70 ) revealed that in vivo NucS would only correct G/T but not A/C mismatches in this species. In this case, transition events in MMR-deficient Δ nucS lines are due to uncorrected G/T mismatches.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, NucS-dependent DSBs may also be repaired by NHEJ in Streptomyces . Very recently, a preprint manuscript ( 70 ) suggested that mycobacterial NucS participates in a MMR reaction involving short patch repair confined within 5–6 bp of the mispaired nucleotides, which appears to be mechanistically distinct from repair by homologous recombination or NHEJ DSB repair mechanisms. A similar study in M. smegmatis , not approved by peer review yet, has also shown that a NucS-promoted DSB is processed by a 5′–3′ exonuclease, but is independent of both RecA, RadA and NHEJ functions Ku and LigD ( 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such striking preference was also observed with NucS from T. kodakarensis ( 9 ) and C. glutamicum ( 20 ,21 ). Furthermore, recent oligonucleotide recombination experiments in M. smegmatis yet to be published ( 70 ) revealed that in vivo NucS would only correct G / T but not A / C mismatches in this species. In this case, transition events in MMR-deficient nucS lines are due to uncorrected G / T mismatches.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that PCNA, which interacts with NucS and the Mre11/Rad50 complexes, may act as a master regulator of the MMR and homologous recombination pathways. Interestingly, in human cells, it has been proposed by (63) suggested that mycobacterial NucS participates in a MMR reaction involving short patch repair confined within 5-6 bp of the mispaired nucleotides, which appears to be mechanistically distinct from repair by homologous recombination or NHEJ DSB repair mechanisms. A similar study in M. smegmatis, not approved by peer review yet, has also shown that a NucS-promoted DSB is processed by a 5'-3' exonuclease, but is independent of both RecA, RadA, and NHEJ functions Ku and LigD (89).…”
Section: Discussionmentioning
confidence: 99%